Comparison of guaranteed state estimators for linear time-invariant systems. (August 2021) - Althoff, Matthias; Rath, Jagat Jyoti
Abstract: Guaranteed state estimation computes the set of possible states of dynamical systems given the bounds of model uncertainties, disturbances, and noises. For the first time, we evaluate and compare a broad class of guaranteed state estimators for linear time-invariant systems regarding scalability, accuracy, and real-time applicability. In particular, we consider strip-based observers, set-propagation observers, and interval observers. The performance of most guaranteed state estimators is significantly affected by the chosen set representation. Zonotopes have emerged as a popular set representation since important operations such as linear maps and Minkowski sum can be computed exactly and efficiently. Furthermore, we provide comparisons with ellipsoids and constrained zonotopes as set representations. The comparison is conducted on various models for state estimation of autonomous vehicles.